SEKALI LAGI TENTANG PENGENTASAN KEMISKINAN (DI BALI) - Windia, Wayan (PIRAMIDA, 2015)
The number of poor households (“RTM”) in Bali Province is still relatively large, reaching 134 804 households. This is also reflected from the persistence of beggars and homeless in urban areas. Poverty is likely to stay there, no matter how poverty alleviation programs have been implemented. In absolute terms this is caused by the tendency of the poverty line used will continue to develop in accordance with the development of the national economy. Poverty alleviation programs in the food sector in the province of Bali apparently less successful when compared with poverty alleviation programs in the fields of education and health.Keywords: poverty alleviation; poor households; absolute poverty
Keywords: pengentasan kemiskinan; rumah tangga miskin; kemiskinan absolut